New insights into the pathology of white matter tracts in cerebral palsy from diffusion magnetic resonance imaging: A systematic review - Scheck, S.; Boyd, Roslyn; Rose, S. (2012)
Aim Structural connectivity analysis using diffusion magnetic resonance imaging (dMRI) and tractography has become the method of choice for studying white matter pathology and reorganization in children with congenital hemiplegia. To evaluate its role in the research domain, we systematically reviewed the literature about children with cerebral palsy (CP) to document common findings and identify strengths and possible limitations of this neuroimaging technology. Method A literature search was performed for peer-reviewed studies pertaining to dMRI and CP. Results Twenty-two studies met the inclusion criteria. The corticospinal tract was studied in greatest detail (18/22). The most common finding was decreased fractional anisotropy and/or increased mean diffusivity, indicating significant loss in the integrity of these corticomotor pathways. Fewer studies assessed ascending sensorimotor pathways including the posterior and superior thalamic radiations, which also showed decreased fractional anisotropy. Anisotropy indices (fractional anisotropy, mean diffusivity) obtained for both corticomotor and sensorimotor tracts were repeatedly shown to correlate with clinical measures. Other tracts studied included commissural and association fibres, which showed conflicting results. Interpretation There is sound evidence that dMRI-based connectivity techniques are useful for improving our understanding of the structure-function relationships of corticomotor and sensorimotor neural networks in CP. © The Authors. Developmental Medicine & Child Neurology © 2012 Mac Keith Press.